2016
DOI: 10.2298/ijgi1603401e
|View full text |Cite
|
Sign up to set email alerts
|

Cruisers on the Danube - the impact of LMX theory on job satisfaction and employees’ commitment to organization

Abstract: In the early 21 st century, tourist cruises along the Danube River (Corridor 7) experience significant expansion. The main task of cruise companies is the satisfaction of guests, which primarily depends on employee satisfaction affected by numerous organizational factors, including the relationship between the employee and the manager as one of the most important. The aim is to examine how the exchange between leaders and followers affects job satisfaction and employee commitment to the organization, is there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Reciprocity plays an important role in manager-employee relationships and links perceived emotional support with behavioral outcomes (Gordon et al, 2019). The idea of leader-member exchange indicates how, in exchange for support, employees may commit to their supervisors (Erdeji et al, 2016). Our study, using SET, argues that managers' emotional competence increases the aesthetic labor of employees.…”
Section: Hypothesis Development Emotional Competence and Aesthetic Labor (Service)mentioning
confidence: 90%
“…Reciprocity plays an important role in manager-employee relationships and links perceived emotional support with behavioral outcomes (Gordon et al, 2019). The idea of leader-member exchange indicates how, in exchange for support, employees may commit to their supervisors (Erdeji et al, 2016). Our study, using SET, argues that managers' emotional competence increases the aesthetic labor of employees.…”
Section: Hypothesis Development Emotional Competence and Aesthetic Labor (Service)mentioning
confidence: 90%
“…Chen et al (2007) conducted their survey on in-group and out-group members and concluded that members of the 'in group' exhibit robust commitment, high degree of performance and job satisfaction whereas members of the 'out group' exhibit lower levels of commitment, performance, and satisfaction. Erdeji et al (2016) provided empirical evidence by investigating how interactions between leaders and subordinates impact job satisfaction and loyalty to the company. 25 crew staff members and 41 managers from Danube River cruise ships took part in the study.…”
Section: Lmx and Organizational Commitmentmentioning
confidence: 99%
“…Dukungan supervisor sebagai bentuk perhatian positif organisasi kepada pekerja dan lingkungan kerja (Erdeji et al, 2016). Dukungan supervisor menjadi aspek penting pada pekerja untuk mencapai sasaran utama, energi, dan sumber daya sosial (Bacharach & Bamberger, 2007;Sinambela et al, 2020).…”
Section: Dukungan Supervisorunclassified